Problems of the co-existence of the protected designations of origin and protected geographical indications: the case „Aceite de Jaén” - Sánchez Jaraba , José Ramón (Przegląd Prawa Rolnego, 2018)
Designations of Origin and Geographical Indications are two quality titles covered by EU legislation for the protection of agricultural products and foodstuffs whose quality is linked to a specific territory. In spite of being two different titles, the similarities between them are evident, and, since the EU regulations do not establish priority or incompatibility between them, it is possible that both protection instruments can apply in the same territory to designate the same type of product. This is actually the case in the province of Jaén, in southeastern Spain, where three Protected Denominations of Origin (PDOs) are threatened as a result of the application for registration of a Protected Geographical Indication (PDI) that intends to act at the provincial level for designating the same product: extra virgin olive oil. In this study we analyse this case and formulate some general recommendations of possible solutions that might allow a peaceful coexistence between these two titles of protection.